The effects of job cognition and personality type on auditor judgment - Wimpie Yustino Setiawan; Tabita Indah Iswari (Jurnal Siasat Bisnis, 2016)
Despite the fact that much research on factors influencing auditor judgment has been carried out, job  cognition and personality type have received little attention from behavioral researches. This study aims to investigate empirical evidence of the effect of job cognition and personality type on auditor judgment. Mail questionnaires were used to collect data from auditors working at public accounting firms in Jakarta and Surabaya.The multiple regression analysis conducted to test the research hypotheses shows that personality type significantly influences auditor judgment. However, the research does not find any empirical evidence that job cognition has a significant effect on auditor judgment.